2018
DOI: 10.1515/jbcpp-2017-0084
|View full text |Cite
|
Sign up to set email alerts
|

An aqueous extract of the Anogeissus leiocarpus bark (AEAL) induces the endothelium-dependent relaxation of porcine coronary artery rings involving predominantly nitric oxide

Abstract: These findings indicate that AEAL is a potent inducer of endothelium-dependent NO-mediated relaxations in porcine coronary arteries through the redox-sensitive Src/PI3-kinase/Akt pathway-dependent activation of eNOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…8-iso-PGF 2α , deriving from ROS/RNS peroxidation of membrane arachidonic acid, represents a stable marker of lipid peroxidation and tissue damage, in vivo [51], whereas the blunting effects on 8-iso-PGF 2α production that are induced by herbal extracts were related to protective effects [48,52]. Consistently with the reported antioxidant effects and the findings by Belemnaba et al [46], the tested extracts blunted LPS-induced 8-iso-PGF 2α production, with the only exception being represented by stem bark MeOH extract. On the other hand, stem bark MeOH extract showed the ability to reduce the level of malondialdehyde (MDA), which is another key marker of lipid peroxidation, in vivo [53].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…8-iso-PGF 2α , deriving from ROS/RNS peroxidation of membrane arachidonic acid, represents a stable marker of lipid peroxidation and tissue damage, in vivo [51], whereas the blunting effects on 8-iso-PGF 2α production that are induced by herbal extracts were related to protective effects [48,52]. Consistently with the reported antioxidant effects and the findings by Belemnaba et al [46], the tested extracts blunted LPS-induced 8-iso-PGF 2α production, with the only exception being represented by stem bark MeOH extract. On the other hand, stem bark MeOH extract showed the ability to reduce the level of malondialdehyde (MDA), which is another key marker of lipid peroxidation, in vivo [53].…”
Section: Discussionsupporting
confidence: 69%
“…Particularly, we selected the concentration 0.1 mg/mL that was at least two-fold lower than LC 50 and in agreement with previous investigations that demonstrated the antioxidant effects on isolated porcine tissue [46]. While considering these findings, we assayed extract effects on rat colon stimulated with LPS, ex vivo, in order reproduce the burden of oxidative stress and inflammation that characterize ulcerative colitis [20,47,48].…”
Section: Resultsmentioning
confidence: 89%
“…It is for this interest that studies have already demonstrated the vasodilation effect of AEAL from Anogeissus leiocarpa. 18 AEAL were also known to be a potent inhibitor of purified cyclic nucleotide phosphodiesterase. 35 A recent study has also shown that a dichloromethane fraction from AEAL has an endothelium-independent vasodilator effect involving inhibition of PDE1, 2 and 5 and involve a reduction in intracellular calcium.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 40 , 41 Indeed, AEAL has been known to have vasodilation properties via Src/PI3-Akt kinase relaxation pathway responsible for the activation of eNOS followed by the release of NO. 18 Moreover, AEAL was known to inhibit in vitro, the purified cyclic nucleotides PDEs found in vascular smooth muscle cell (VSMC), whose might induce vessels relaxation. 35 Previous studies raised the presence of tannins, sterols and triterpenoids in AEAL, which were known to have vasodilator effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation